A new species of the Callophrys mystaphia Miller, 1913—group from Iran (Lepidoptera: Lycaenidae: Eumaeini) - Krupitsky, Anatoly V.; Kolesnichenko, Kirill A. (Zootaxa, 2013)
A new species, recently misinterpreted as Callophrys mystaphia Miller, 1913, Callophrys mystaphioides Krupitsky & Kolesnichenko sp. n., is described from Central Iran (Esfahan Province). The new species differs from C. mystaphia in the combination of external characters and morphology of genitalia. Possible relations of C. mystaphia—species group with other Palaearctic Callophrys are discussed.